ANALISIS FAKTOR NISBAH DAN FAKTOR SUKU BUNGA RATA-RATA KREDIT MODAL KERJA BANK KONVENSIONAL YANG MEMPENGARUHI JUMLAH PEMBIAYAAN BAGI HASIL PADA BANK DAN UNIT USAHA SYARIAH DI INDONESIA PERIODE 2005 SAMPAI 2010 - Noviantoro, Rinto (Ekombis Review, 2016)
Rinto Noviantoro; This study aims to determine how big the analysis of each factor, both of ratio and interest rates affect the amount of financing for the results at the Islamic Bank for the period 2005 to 2010.Metode analysis used a correlation method. The variables studied were the profit sharing ratio is rightfully bank and interest rate factor The results showed that the variables used are ratio and interest together can influence the variable amount of financing for the results. From the results if the data  is  not  there  multikolineraritas,  the  heterokedastilitas,  there are  positive  auto  and  normal distribution of data Keywords: Ratio, lending and financing for the results.